REDISTRIBUCIÓN DE LA CONFIGURACIÓN GEOMÉTRICA DE MAMPOSTERÍA EN EDIFICACIONES DE CONCRETO ARMADO PARA REDUCIR LA EXCENTRICIDAD DE PISO - Centeno Yambay, Juan Carlos (2019)
The predominant typology of constructions in our environment consist of framed structures of reinforced concrete, filled with masonry walls, these are used for the interior division of environments to make the exterior enclosure. The inclusion of masonry walls generates changes in the center of mass, and if these are located in the porticos, their rigidities change during the first cycles of an earthquake. This problem causes eccentricities that generate the phenomenon known as torsion in a plant, an event that can cause severe structural damage. In spite of this, generally, these elements are not considered in the analysis of buildings. In the present work, the reduction of the eccentricities generated by the presence of masonry was proposed through a combination of different types of materials and their redistribution. For this, we considered three types of masonry that were used in our environment (brick, block, and gypsum). Different types of masonry of structural configurations modeled without walls were analyzed, and the results were compared with those obtained by modeling the structures with walls. The combinations of walls with different physical and mechanical properties and their redistribution, allowed to significantly reducing the eccentricities produced by using a single type of masonry